Asteraceae Artemisia campestris and Artemisia herba-alba Essential Oils Trigger Apoptosis and Cell Cycle Arrest in Leishmania infantum Promastigotes - Aloui, Zohra (Evid Based Complement Alternat Med, 2016)
We report the chemical composition and anti-Leishmania and antioxidant activity of Artemisia campestris L. and Artemisia herba-alba Asso. essential oils (EOs). Our results showed that these extracts exhibit different antioxidant activities according to the used assay. The radical scavenging effects determined by DPPH assay were of IC(50) = 3.3 mg/mL and IC(50) = 9.1 mg/mL for Artemisia campestris and Artemisia herba-alba essential oils, respectively. However, antioxidant effects of both essential oils, determined by ferric-reducing antioxidant power (FRAP) assay, were in the same range (2.3 and 2.97 mg eq EDTA/g EO, resp.), while the Artemisia herba-alba essential oil showed highest chelating activity of Fe(2+) ions (27.48 mM Fe(2+)). Interestingly, we showed that both EOs possess dose-dependent activity against Leishmania infantum promastigotes with IC(50) values of 68 μg/mL and 44 μg/mL for A. herba-alba and A. campestris, respectively. We reported, for the first time, that antileishmanial activity of both EOs was mediated by cell apoptosis induction and cell cycle arrest at the sub-G0/G1 phase. All our results showed that EOs from A. herba-alba and A. campestris plants are promising candidates as anti-Leishmania medicinal products.